Aplicações de um potencial reativo no estudo da interação entre moléculas e superfícies bidimensionais - Carneiro, Bárbara Pinto [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In materials science, the search for technological improvements have become one of the main subject of study of researchers. This is especially true in the case of materials with reduced sizes, in the nanometer scale. Important phenomena to be studied in these cases are the desorption and adsorption on two-dimensional materials, such as graphene. These phenomena are of great importance in the study of interactions between organic films, synthesis or catalysis of reactions on surfaces and even in the creation of nanoscale devices [1, 2, 3, 4]. Between the most important topics related to these phenomena are the storage of gases in low-dimensional systems and the study of nanostructured fuel cells or batteries. In this context we used two different parametrizations for the reactive force field ReaxFF to study the potential barriers and reaction barriers of our system. First we made a study about the Reaction Barriers and Energy Barriers for bonds between graphene and the following atoms: sulfur, fluorine, hydrogen, nitrogen and oxygen. It is important to have this information in order to make it possible to understand how these atoms react with the graphene sheet. Subsequently, we calculate reaction barriers for mixed structures where fluorine is a fixed element bonded to graphene and other element is simultaneously bonded to graphene. This other element (N, O, H or S) is varied in its possible relative positions (ortho, meta and para in relation to fluorine in either: the same side and in the opposite side of the graphene membrane)

A busca por melhorias tecnológicas no âmbito dos novos materiais tem se tornado alvo dos pesquisadores, principalmente materiais de tamanhos reduzidos, em escala nanométrica. Alguns dos fenômenos mais importantes a serem estudados nestes casos são o de dessorção e adsorção em materiais bidimensionais, como o Grafeno. Esses fenômenos têm grande importância no estudo de interações entre filmes orgânicos, síntese ou catálise de reações em superfícies e até mesmo em criação de dispositivos em nanoescala [1, 2, 3, 4]. Entre os tópicos de maior importância ligados a estes fenômenos estão o armazenamento de gases em sistemas de baixa dimensionalidade e o estudo de células combustíveis ou baterias nanoestruturadas. Neste contexto utilizamos duas parametrizações diferentes do potencial reativo ReaxFF, para fazer o estudo das barreiras de reação e de energia do nosso sistema. Primeiramente fizemos um estudo sobre as Barreiras de Reação e as Barreiras Energia para as ligações entre os seguintes átomos: enxofre, flúor, hidrogênio, nitrogênio e oxigênio sobre folhas de grafeno. É importante ter essa primeira informação para que possamos entender como esses átomos sozinhos reagem à folha de grafeno. Posteriormente calculamos as barreiras de reação e ligação de estruturas mistas, tendo o flúor como elemento fixo e variando os demais elementos entre as possíveis posições relativas (orto, meta e para no plano do flúor e orto, meta e para do no plano oposto ao flúor)
Keywords: Nanotecnologia; Adsorção; Grafeno; Físico-química; Atomos